THE MEANING OF WAR AND PEACE FOR THE MIGRANT SYRIAN STUDENTS AT TERTIARY LEVEL IN TURKEY: AN ART-BASED STUDY - Egüz, Şule (International Online Journal of Education and Teaching, 2020)
The present study aimed to determine the definition of war and peace by the migrant Syrian students at tertiary level; their image of war via their artistic drawings, as well as to reveal their expectations from peace. For this purpose, the study was conducted in the 2018-2019 academic year with an art-based research approach, employing art as a method, a form of analysis and as an object. The participants comprised 25 Syrian students between the age range of 17-20 years old who emigrated from Syrian war zones to Turkey. The analysis of the data focused on the definitions of war and peace, Syrian students’ drawings, and their verbal expressions about the drawings that help develop an analytical framework. The findings of the study demonstrated that most of the drawings reflected real images of war and peace; the participants rendered both visual and verbal symbolizations as the main expression of their suffering during the war and longing for peace. The drawings provided clues that could help them cope with the possible traumatic incidents they could experience at the present or in the future, and preserve their identity destructed by factors out of their control. Keywords: Syria, war, peace, art, Syrian students, tertiary level, immigrants